Association of obesity with anxiety, depression and emotional well‐being: a community survey - Anthony F. Jorm; Ailsa E. Korten; Helen Christensen; Patricia A. Jacomb; Bryan Rodgers; Ruth A. Parslow (Elsevier, 2003)
Abstract Objective:To investigate the association of obesity with anxiety, depression and emotional well‐being (positive and negative affect) in three age groups. Methods:A cross‐sectional survey was carried out in Canberra and the neighbouring town of Queanbeyan, Australia, with a random sample from the electoral roll of 2,280 persons aged 20-24, 2,334 aged 40-44, and 2,305 aged 60-64. Results:Self‐reported height and weight were used to classify participants as underweight (body mass index of less than 18.5), acceptable weight (18.5 to less than 25), overweight (25 to less than 30) or obese (30 and over). Obesity in women was associated with more anxiety and depression symptoms and less positive affect, but there were only weak and inconsistent associations in men. When factors that might mediate any association were controlled (physical ill health, lack of physical activity, poorer social support, less education and financial problems), a different picture emerged, with the underweight women having more depression and negative affect and the obese and overweight women tending to have better mental health than the acceptable weight group. Controlling for physical ill health alone accounted for the association of obesity with anxiety and depression in women. Conclusions:Obesity has an association with anxiety, depression and lower well‐being in women, but not in men. The results are consistent with physical ill health playing a mediating role. Implication:Reducing obesity in the population is unlikely to have any direct effect on mental health or emotional well‐being.